Power system stability and control: a comprehensive review focusing on the rotor angle case - Mohamad Murad, Nor Syaza Farhana; Kamarudin, Muhammad Nizam; Md Rozali, Sahazati; Zakaria, Muhammad Iqbal (Bulletin of Electrical Engineering and Informatics, 2024)
This paper provides a review of power system stability, focusing on the rotor angle case. To gain a preliminary understanding of the stability studies, the discussion begins with an overview of generators in power system generation. The distinguishing parameters of synchronous generators as compared to their counterparts such as induction generators, inductor alternators, and direct current generators are also emphasized. The discussion that is not bounded within their stability issues and control strategies is briefly assessed. The shortcomings and advantages of various modeling approaches are also discussed therein. To extend the thoughts, this review includes a thorough discussion and classification of power system stability, which includes rotor angle stability, frequency stability, and voltage stability. The stability of the rotor angle is important as it ensures frequency stability and voltage stability. This paper also presents the power system modeling approach that is able to facilitate the rotor angle stability studies. This paper also aims to review the established rotor angle stabilizers and algorithms developed by previous researchers.